In memoriam. Orlando Zelaya-Angel’s contributions in Superficies y Vacío (Superficies y Vacío, 2021)
Professor Orlando Zelaya Angel was an outstanding member of the research community on Solid State Physics. He served as President to the Sociedad Mexicana de Ciencia de Superficies y Vacío (SMCSyV; currently Sociedad Mexicana de Ciencia y Tecnología de Superficies y Materiales – SMCTSM), for the period 1995-1996. Professor Zelaya formed many researchers in Mexico, who continue developing research, either in Mexico, in their countries of origin, or abroad.Throughout the evolution of Superficies y Vacío, Professor Zelaya, contributed with sixteen articles on subjects ranging from thin films for optoelectronic applications, through hard coatings and studies on the process for production of Tortillas; covering most of his research areas of interest. Here is a subject-chronological compilation of the abstracts to his articles in Superficies y Vacío, after a year of his departure.